(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2025)
Allergic rhinitis (AR) is a common and increasingly diagnosed chronic inflammatory condition in children, often associated with environmental allergen exposure and immune dysregulation. Recent studies suggest that the nasopharyngeal microbiome, a crucial player in mucosal immunity, may be involved in modulating susceptibility to allergic inflammation. This study aims to investigate the microbial signatures and associated immune patterns in the nasopharynx of pediatric patients with allergic rhinitis. A cross-sectional observational study was conducted involving 50 children aged 3 to 12 years with clinically confirmed allergic rhinitis and 30 healthy, age-matched controls. Nasopharyngeal swabs were collected and analyzed using 16S rRNA gene sequencing. Microbial diversity, community composition, and relative abundance of key taxa were evaluated. Serum IgE levels and nasal eosinophil counts were assessed to correlate immune responses with microbial data. Children with allergic rhinitis exhibited a distinct dysbiotic pattern characterized by decreased microbial diversity and significant enrichment of pro-inflammatory taxa such as Moraxella catarrhalis, Haemophilus influenzae, and Staphylococcus aureus. Concurrently, beneficial commensals like Dolosigranulum pigrum and Corynebacterium accolens were significantly reduced. These microbial changes were positively associated with higher serum IgE concentrations and elevated eosinophil counts, suggesting a link between microbial imbalance and immune activation. The findings indicate that nasopharyngeal microbiome alterations may contribute to or reflect the immune dysregulation seen in pediatric allergic rhinitis. Identification of specific microbial markers could serve as a basis for microbiome-informed diagnostics and preventive strategies. This study adds novel insight into the role of nasopharyngeal microbial communities in shaping allergic inflammation in children and proposes potential microbial targets for future interventions.